Obesity-induced overexpression of miR-802 impairs insulin transcription and secretion - Fangfang Zhang (Nature Portfolio, 2020)
Obesity predisposes to type 2 diabetes, but the mechanisms of obesity-associated β cell dysfunction are incompletely understood. Here the authors report that obesity increases the levels of miR-802, which impairs insulin transcription and secretion by targeting NeuroD1 and Fzd5.